Experimental evaluation of the viscoelasticity of porcine vitreous. Issue 175 (3rd February 2021) - Aboulatta, Ali; Abass, Ahmed; Makarem, Ahmed; Eliasy, Ashkan; Zhou, Dong; Chen, Duo; Liu, Xiaoyu; Elsheikh, Ahmed
Abstract : This study aims to estimate the material properties of the porcine vitreous while testing it in close to its natural physiological conditions. Eighteen porcine eyes were tested within 48 h post-mortem. A custom-built computer-controlled test rig was designed to support, load and monitor the behaviour of eye globes while being subjected to dynamic rotation cycles mimicking saccade eye movement. Specimens were glued to the base of a container, surrounded by gelatin, frozen and cut in half to expose the vitreous. After thawing, the container was subjected to concentric dynamic rotations of up to 5°, 10° or 15°, while taking 50 MP photos of the specimen every 2 ms. The images were analysed by a digital image correlation algorithm to trace the movement of marked points on the vitreous surface with different radii from the centre of the posterior chamber. The initial camera image was used in building a finite-element model of the test set-up, which was used in an inverse analysis exercise to estimate the material properties of the vitreous. Angular displacements of the monitored points were up to 3.3°, 4.1° and 3.9° in response to eye rotations of 5°, 10° and 15°, respectively. With the experimental relationships between eye rotation and angular displacements used as target behaviour, the inverse analysis exercise estimated the initial shear modulus, the long-term shear modulus and the viscoelastic decay constant of the porcine vitreous as 2.10 ± 0.15 Pa, 0.50 ± 0.04 Pa and 1.20 ± 0.09 s −1, respectively. Consideration of the viscoelasticity of the vitreous was essential to represent its experimental behaviour. Testing the vitreous in close to its normal physiological conditions produced estimations of the initial shear modulus and long-term shear modulus that were, respectively, smaller and larger than reported values (Zimberlin et al . 2010 Soft Matter 6, 3632–3635. (doi:10.1039/b925407b ), Liu et al . 2013 J. Biomech. 46, 1321–7. (doi:10.1016/j.jbiomech.2013.02.006), Rossi et al . 2011 Invest. Ophthalmol. Vis. Sci. 52, 3994–4002. (doi:10.1167/iovs.10-6477 )).